ANALYSIS SAFETY FACTOR KUALANAMU RAILWAY EMBANKMENT USING FINITE ELEMENT METHOD - Surbakti, Rudianto (Universitas Medan Area, 2024)
Analysis of the soil's bearing capacity for the loads acting on the railway tracks is one of the most important parts of planning the structure of the railway to be built. Considering that train activity is very intense and imposes a significant live load on the soil layer beneath it, it is necessary to ensure that the soil layer under the railroad track is able to withstand the entire load. This analysis aims to ensure that the subgrade is able to support the entire load acting on it by calculating the safety factor for the layers of soil and ballast on the railroad track. The calculation method used to obtain the load value is analytical, while the calculation of safety factors and soil settlement is carried out using the finite element method (FEM) calculation concept. From the results of analysis using the finite element method (FEM) using Plaxis 2D, it can be concluded that at the operational stage the maximum drop in the vertical direction was -5.96 mm while the maximum movement in the horizontal direction was 1.12 cm. This is smaller than the maximum drop permitted by Minister of Transportation Regulation No. 60 of 2012, namely 10 cm. The safety factor during train operations is 2.902, so the railroad construction can be declared safe.